Experimental Study on Mechanical Performance of U-Shaped Steel-Encased Concrete Composite Beam-Girder Joints - Zhangqi Hu; Ran He; Yukui Wang; Weirong Lv; Jingchao Li (Advances in Civil Engineering)
This paper proposes a novel U-shaped steel-encased concrete composite beam-girder joint (referred to herein as the novel composite beam-girder joint), in which the U-shaped beams at two sides (L and R) are inserted into a shaped sleeve, and the U-shaped girder and two U-shaped beams are connected by the shaped sleeve through welding. Compared with the traditional beam-girder joints, the novel composite beam-girder joints take advantage of easy construction, light weight, and short construction period. The failure patterns, load-strain and load-deflection curves, and strain distributions of the novel composite beam-girder joints were investigated through the static loading tests on two full-scale specimens, denoted as GBJ1 and GBJ2. The two specimens were varied in beam section reinforcements. Specimen GBJ2 was equipped with 3Ф16 additional bars in the U-shaped beams based on Specimen GBJ1. Test results show that the two specimens failed as the through arc cracks developed at the concrete slab interfaces. The additional bars can increase the bearing capacity slightly but will also increase the stress concentration on the bottom flange of the shaped sleeve, leading to the decrease of ductility for Specimen GBJ2. The slab effect is considered in the test and can thus reflect the actual stress state of the beam-girder joints well. This study can provide a reference for the design and application of beam-girder joints.